(untitled) (Asian Business Research, 2017)
In selling products is thee main thing too note, because of the appeal of consumer products will be a consideration in buying consumer goods. The appeal may be packaging, taste, price, volume or other product attributes. To cultivate the right product attributes required preferences of consumers. The purpose of this research is to know the attributes and combinations of product attributes Borneo Hive the most preferred by consumers. This research uses a quantitative approach with an analysis conjoint use SP program 20.0. The sample used inn this study is 500 consumers ever buy Borneo Hive and product attributes are examined is the packaging, volume and price. The results of this study showed that the most preferred product attributes consumers Borneo Hive is e volume off packaging and rices followed. And for the most preferred attribute combination is the glass packaging with a volume of 500 ml - 3350 ml with the price of IDR 30,000 - IDR 40,000.